2022 IEEE 32nd International Workshop on Machine Learning for Signal Processing (MLSP) 2022
DOI: 10.1109/mlsp55214.2022.9943405
|View full text |Cite
|
Sign up to set email alerts
|

Fish Feeding Intensity Assessment in Aquaculture: A New Audio Dataset AFFIA3K and a Deep Learning Algorithm

Abstract: Fish feeding intensity assessment (FFIA) aims to evaluate the change of fish appetite during the feeding process, which is potentially useful in industrial aquaculture. Previous methods are mainly based on computer vision techniques. However, these methods are limited by water refraction and uneven illumination. In this paper, we introduce a new approach for FFIA using audio. We create a new audio dataset for FFIA, namely AFFIA3K, which contains 3000 labelled audio clips of different fish feeding intensity (No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 76 publications
0
0
0
Order By: Relevance
“…The growth, health, and sustainability of aquaculture depend on fish-feeding behavior [ 16 , 19 ]. Researchers can improve fish growth by studying their feeding behavior, while reducing waste and environmental impact.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth, health, and sustainability of aquaculture depend on fish-feeding behavior [ 16 , 19 ]. Researchers can improve fish growth by studying their feeding behavior, while reducing waste and environmental impact.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They achieved 85.9% accuracy, representing substantial progress toward using deep learning to decode aquaculture-related actions. Cui et al [ 19 ] leveraged Mel Spectrogram features and a convolutional neural network to classify fish feeding behaviors, obtaining a mean average precision of 74%. This measure considers both precision and recall rather than mere accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One is the fish density analysis dataset (DlouFishDensity), which contains 20 side-shot videos with complete fish feeding behavior, as shown in Figure 11. Another is a data video clip taken by Cui (Cui et al, 2022), which contains videos all taken above the water surface, as shown in Figure 12.…”
Section: Experimental Datasetmentioning
confidence: 99%
“…The videos that meet our requirements have a resolution of 1920*1080 and a duration between 30s-60s. Second, we manually labeled the locations of fish heads on 900 image frames in DlouFishDensity and 300 image frames in the video of Cui (Cui et al, 2022) dataset, and finally labeled the locations of more than 30000 fish heads. The labeling tool uses MATLAB to establish a data_marker labeling applet to label the fish head of each picture in the data set.…”
Section: Experimental Datasetmentioning
confidence: 99%
See 1 more Smart Citation